Islam and the Green Economy in Review of Sharia Principles for Sustainable Business Practices - Kaswoto, Junet; Simamora, Mukti; Rijadi, Puti Khairani; Ramdani, Safier; Sudarmanto, Eko (West Science Islamic Studies, 2025)
This study reviews the intersection of Islamic principles and green economy practices, emphasizing how Sharia law can guide sustainable business operations. Using a literature review approach, 15 scholarly articles from Google Scholar were analyzed to identify key Sharia-based concepts—such as stewardship (khalifah), avoidance of waste (israf), ethical investment, and social responsibility—that support environmentally sustainable and socially responsible business practices. The findings reveal that integrating Sharia principles into corporate strategies promotes ecological preservation, ethical governance, and long-term economic resilience. Practical approaches highlighted include Sharia-compliant financing, green supply chain management, and eco-friendly corporate governance. This study underscores the potential of Islamic jurisprudence as a framework for advancing the green economy, offering insights for scholars, policymakers, and business practitioners seeking to harmonize religious ethics with sustainable development.